Detection of Pseudomonas syringae pv papulans in apple budwood - Vanneste, J.L.; Yu, J. (New Zealand Plant Protection, 2006)
Pseudomonas syringae pv papulans (Psp) causes blister spot on apples an economically important disease of the cultivar Mutsu in eastern North America Neither the pathogen nor the disease has been recorded in New Zealand or Australia Since Psp can be transmitted via budwood a protocol to specifically detect Psp in apple buds has been developed It is based on the amplification by polymerase chain reaction (PCR) of part of the hrpL gene Using this protocol presence of Psp could be routinely detected in apple buds spiked with 100 cells of the pathogen This protocol was used to analyse budwoods from Hawkes Bay and Waikato and apple fruit from Waikato Hawkes Bay and Central Otago All samples were negative which is consistent with the pathogen never having been recorded in this country